PROBLEMATIKA GURU DALAM MENGEMBANGKAN MEDIA PEMBELAJARAN BERBASIS MULTIMEDIA DI SD/MI - Yani Pratwi; Aninditya Sri Nugraheni (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
Multimedia-based learning media is very important to be developed in order to support the continuity of the learning process. However, teacher experience problems when they intend to develop multimedia-based learning media and the teachers often use existing learning media. Hence, the research in this article will discuss the problems of teachers in developing multimedia-based learning media and the efforts that should be applied at MIN 2 South OKU in order to ease teachers to develop multimedia-based learning media. The research method used was a qualitative research method based on field research. The research was conducted at MIN 2 South OKU, which involved the principal, teachers, and students at the school. It was obtained that the results of the teachers’ problems in developing multimedia- based learning media in elementary schools were 1) not having much time, 2) difficulty in using digital editor tools, 3) the ages, 4) cost that was quite expensive, 5) lack of knowledge, and 6) network constraints and efforts that should be made to minimize the existing problems through conducting training, mutual cooperation among the teachers, discussing the funds for learning media, and giving appreciation.